Cost-Effective Medical Robotic Telepresence Solution using Plastic Mannequin - Victor O. Matthews; Segun I. Popoola; Aderemi A. Atayero; Emmanuel Adetiba; Joke A. Badejo (Institute of Advanced Engineering and Science, 2017)
Robotic telepresence is an Information and Communication Technology (ICT) solution that has a huge potential to address the problem of access to quality healthcare delivery in rural areas. However, the capital and operating costs of available systems are considered to be unffordable for rural dwellers in emerging economies. In addition, most of these communities are not even connected to the power grid. In this paper, the authors reduced the cost of engaging a robotic telepresence solution for rural medicare by using plastic mannequin and solar photovoltaic technology. An IP camera was fixed in each of the eye sockets of the plastic mannequin. These cameras are connected to a mini-computer embedded in the plastic mannequin. A Wi-Fi module establishes an Internet connection between remote physicians and rural heathcare facilities. The system is powered by a solar photovoltaic energy source to guarantee power availability. Another unique feature of this solution is that it gives the patient a better impression of the physical presence of a physician. Comparative cost analysis with robotic telepresence available in the market showed that our system is more affordable. This development will increase the adoption of robotic telepresense in rural telemedicine.